Prospective evaluation of cardiac ultrasound performance by general internal medicine physicians during a 6-month faculty development curriculum - Christopher J. Smith; Abdulrahman Morad; Christopher Balwanz; Elizabeth Lyden; Tabatha Matthias (Critical Ultrasound Journal, 2018)
Abstract Background Point-of-care (POCUS) education is rapidly expanding within medical schools and internal medicine residency programs, but lack of trained faculty is a major barrier. While POCUS training can improve short-term outcomes, knowledge and skills rapidly decay without deliberate practice and feedback. The purpose of this study was to evaluate the performance of focused cardiac ultrasound (FCU) by volunteer general internal medicine (GIM) faculty participating in a longitudinal POCUS curriculum. Methods Participants: Nine GIM clinician-educators participated in a 6-month POCUS curriculum. Faculty performance was compared to three cardiology fellows. Three diagnostic cardiac sonographers (DCS) were also evaluated and served as the gold standard. Evaluation: the primary outcome was a FCU efficiency score, calculated by dividing image quality score by exam duration. FCU exams were conducted on three standardized patients after completion of an introductory workshop, at 3 months, and at 6 months. Two blinded cardiologists scored the exams. Analysis: mean efficiency scores were compared using a linear mixed effects model, followed by pairwise comparisons using Tukey’s test. Results GIM faculty’s FCU efficiency scores were maintained over the 6-month period (2.2, SE 1.0 vs. 3.8, SE 1.0, p = 0.076). Their scores at each session were similar to cardiology fellows (p > 0.69), but inferior to DCSs (p < 0.0001). Conclusion GIM faculty participating in a POCUS curriculum maintained their FCU performance over 6 months with efficiency scores comparable to experienced cardiology fellows.